Penitencjarne i pozapenitencjarne aspekty zachowań suicydalnych w warunkach izolacji więziennej - Lenart-Kłoś, Katarzyna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2025)
Suicidal behaviour among prisoners is one of the most challenging issues facing the prison system, as isolation, violence, mental disorders and a lack of social support generate an environment conducive to the escalation of suicidal thoughts and attempts. In Poland, there is still a lack of comprehensive analyses combining the penitentiary and post-penitentiary perspectives on this phenomenon. The aim of this article is to identify risk factors for suicidal behaviour in prison isolation and after release from penitentiary units. The analysis is based on desk research, including statistical data, reports from penitentiary institutions, normative acts, and the results of domestic and foreign studies. Suicidal behaviour in prisons is multifactorial. Age, sex, mental disorders, traumatic experiences, stage of imprisonment, overcrowding, isolation, lack of contact with loved ones and such social crises as the COVID-19 pandemic are all relevant factors. The period immediately after release from prison is also associated with a high risk. Effective suicide prevention in penitentiary units requires regular risk monitoring, staff training, early identification of threats, and ensuring that psychological suport is continued after the sentence is served.